Experimentally derived efficiency and exergy analysis of a new solar air heater having different surface shapes - Benli, Huseyin (Pergamon-Elsevier Science Ltd, 2013)
The aim of this study is to provide a remedy for the low thermo-physical properties of air which is used as different absorber surface of air heater. This paper presents an experimental investigation on the absorber surface of the collector whose shape and arrangement were made up to provide better heat transfer surfaces. In the study an experimental performance and exergy analysis of five types of air heating solar collectors: corrugated trapeze, reverse corrugated, reverse trapeze, and a base flat-plate collector are presented. The results of the experiments were evaluated at the same time of the days with the same radiation. The efficiencies were determined for the collectors and comparisons were made among them. The present data showed that heat transfer coefficient and pressure drop increase with shape of absorbers surface. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Solar air collector; Collector efficiency; Exergy loss; Thermal efficiency